High-frequency stimulation of afferent axons alters firing rhythms of downstream neurons - Weijian Ma, Zhouyan Feng, Zhaoxiang Wang, Wenjie Zhou (Journal of Integrative Neuroscience, 2019)
Deep brain stimulation is an emerging treatment for brain disorders. However, the mechanisms of high-frequency brain stimulation are unclear. Recent studies have suggested that high-frequency stimulation might produce therapeutic effects by eliminating pathological rhythms in neuronal firing. To test the hypothesis, the present study investigated whether stimulation of axonal afferent fibers might alter firing rhythms of downstream neurons in in-vivo experiments with Sprague-Dawley rats. Stimulation trains of 100 Hz with one minute duration were applied to the Schaffer collaterals of hippocampus Area CA1 in anaesthetized rats. Spikes of single interneurons and pyramidal neurons in the downstream region were analyzed. The spike rhythms before, during, and after the stimulations were evaluated by analyzing the power spectrum density of autocorrelograms of the spiking sequences. The rhythms of local field potentials were also evaluated by power spectrum density. During baseline recordings, theta rhythms were obvious in the spiking sequences of both types of neuron and in the local field potentials of the stratum radiatum. However, these theta rhythms were all suppressed significantly during the stimulations. Additionally, the results of Pearson's correlation analysis showed that 20-30% variation in the theta rhythms of neuronal firing could be explained by changes of the theta rhythms in local field potentials. High-frequency axonal stimulation might prevent the original rhythmic excitation in afferent fibers and generate new excitation by stimulation pulses per se, thereby suppressing the theta rhythms of individual neuron firing and of local field potentials in the region downstream from stimulation. The results provide new evidence to support the hypothesis that high-frequency stimulation can alter the firing rhythms of neurons, which may underlie the therapeutic effects of deep brain stimulation.